Understanding the Role of Sociocultural Influences on Entrepreneurial Activities: a Study of Ukrainian Women War Refugees in Poland - Katarzyna Gadomska-Lila; Anna Ścibior-Butrym (European Management Studies)
Purpose: The aim of the article is to identify the socio-cultural determinants of entrepreneurial activities of Ukrainian refugee women in Poland. The manuscript points out the complexity of the phenomenon of entrepreneurship as an important element of economic adaptation of women experiencing migration and presents the results of empirical research. Design/methodology/approach: the research conducted was exploratory in nature, carried out using qualitative methods. Two focus group interviews were conducted with 16 female respondents. Findings: The analysis of the collected research material reveals the multidimensionality of the socio- -cultural aspects of the entrepreneurial activities of Ukrainian refugee women in Poland, particularly highlighting such factors as the value system, entrepreneurial traditions, risk propensity, social relations and entrepreneurial competences. Research limitations/implications: despite significant findings regarding the importance of socio-cultural determinants of the development of entrepreneurial activities of Ukrainian refugee women in Poland, the presentation of the perspective of one group, as well as the cultural context, may be a limitation of the research conducted. Originality/value: The data obtained were classified into groups of factors stimulating and blocking the entrepreneurship of Ukrainian refugee women. In addition, the results of the research made it possible to present a fairly wide spectrum of pro-entrepreneurial initiatives that can provide recommendations for aid organisations, institutions working for the adaptation of persons in a migratory situation, as well as employers who employ these persons.